Strategi Komunikasi Dakwah KODASA (Korps Dakwah Santri) Pondok Pesantren Darussalam Blokagung Banyuwangi - Anas, Ahmad Rosyid; Agus Baihaqi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This research discusses the communication strategies of preaching applied by the Santri Preaching Corps (KODASA) at the Darussalam Islamic Boarding School in Blokagung Banyuwangi in conveying Islamic values to students and the community. Using a descriptive qualitative approach, this study aims to identify the forms of KODASA's communication strategies, analyze the media and methods used, and evaluate the supporting and hindering factors in their implementation. The theoretical foundation used is the theory of preaching communication, particularly the persuasive communication model and the two-step flow communication model. Data collection techniques include field observations, in-depth interviews with KODASA members and supervisors of the boarding school, as well as documentation of preaching activities. The results of the study indicate that KODASA implements a communication strategy that is humanistic and contextual, using methods such as lectures, training, interactive discussions, and the utilization of YouTube media. The real impact of the strategies implemented by Kodasa is evident in the increased understanding and participation of students in religious activities. Supporting factors include is full support from the pesantren and the enthusiasm of the students, while the inhibiting factors are limited media facilities and a lack of enthusiasm from the community. This study emphasizes the importance of adaptive and collaborative communication strategies in strengthening pesantren-based preaching.